Pseudoepitheliomatous Hyperplasia: Relevance in Oral Pathology - Sarangarajan, R (J Int Oral Health, 2015)
Pseudoepitheliomatous hyperplasia (PEH), a neglected entity by oral pathologist possesses utmost importance in the field of research. Of all the investigative challenges, PEH, a reactive epithelial proliferation is seen secondary to lesions with infectious, inflammatory, reactive, and degenerative origin. Small sized samples, incomplete excision, improper orientation, and dense inflammatory changes render diagnostic confront to the oral pathologist in exclusion of frankly invasive malignant lesions like squamous cell carcinoma from lesions exhibiting PEH. The diagnosis can occasionally be difficult as they mimic other lesions also, on clinic-pathological assessment. Thus, this article gives an insight regarding the various concepts of etiopathogenesis, histopathology, differential diagnosis, and malignant potential of PEH. A combined effort of a clinician and pathologist benefits every patient to rule out malignancy and render appropriate treatment as the only local conservative approach is essential to remove PEH associated lesions.